Browning of Human Subcutaneous Adipose Tissue after Its Transplantation in Nude Mice. Issue 2 (August 2018) - Qiu, Lihong; Zhang, Zhaoxiang; Zheng, Hui; Xiong, Shaoheng; Su, Yingjun; Ma, Xianjie; Yi, Chenggang
Abstract : Background: The clinical unpredictability of autologous fat grafting originates partially from the unique characteristics of adipose tissue. Evidence of adipose remodeling toward browning (developing of brown-like adipocytes in white adipose tissue) in response to trauma has been emerging. With regard to fat grafting surgery by which adipose tissue depots are directly and ubiquitously traumatized, whether it affects adipose phenotype change toward browning has not been previously reported. Methods: Human subcutaneous adipose tissues were harvested from the abdominal region of female patients by means of liposuction and were then injected into the dorsal flanks of athymic nude mice. After 12 weeks, fat grafts were harvested and subjected to histologic analysis. Results: Hematoxylin and eosin staining showed the appearance of small multilocular adipocytes in the peripheral region of the grafts. These adipocytes exhibited higher staining for uncoupling protein 1 (a fat browning–specific marker), mitochondrial protein, and CD31 compared with the central ones, indicating the presence of brown-like adipocytes (i.e., beige adipocytes) in this area. Furthermore, immunofluorescence staining demonstrated that these beige adipocytes might be derived from de novo adipogenesis from progenitors of graft origin. Conclusion: Results of this study suggest that browning of subcutaneous white adipose tissue participates in adaptive tissue remodeling following grafting and contributes to adipose tissue repair.